A systematic review and meta-analysis of minimally invasive total mesorectal excision versus transanal total mesorectal excision for mid and low rectal cancer - Gang, Du Yong; Dong, Lin; DeChun, Zhang; Yichi, Zhang; Ya, Lu (Frontiers in Oncology, 2023)
Abstract Background: Minimally invasive total mesorectal excision (MiTME) and transanal total mesorectal excision (TaTME) are popular trends in mid and low rectal cancer. However, there is currently no systematic comparison between MiTME and TaTME of mid and low-rectal cancer. Therefore, we systematically study the perioperative and pathological outcomes of MiTME and TaTME in mid and low rectal cancer. Methods: We have searched the Embase, Cochrane Library, PubMed, Medline, and Web of Science for articles on MiTME (robotic or laparoscopic total mesorectal excision) and TaTME (transanal total mesorectal excision). We calculated pooled standard mean difference (SMD), relative risk (RR), and 95% confidence intervals (CIs). The protocol for this review has been registered on PROSPERO (CRD42022374141). Results: There are 11010 patients including 39 articles. Compared with TaTME, patients who underwent MiTME had no statistical difference in operation time (SMD -0.14; CI -0.31 to 0.33; I2=84.7%, P=0.116), estimated blood loss (SMD 0.05; CI -0.05 to 0.14; I2=48%, P=0.338), postoperative hospital stay (RR 0.08; CI -0.07 to 0.22; I2=0%, P=0.308), over complications (RR 0.98; CI 0.88 to 1.08; I2=25.4%, P=0.644), intraoperative complications (RR 0.94; CI 0.69 to 1.29; I2=31.1%, P=0.712), postoperative complications (RR 0.98; CI 0.87 to 1.11; I2=16.1%, P=0.789), anastomotic stenosis (RR 0.85; CI 0.73 to 0.98; I2=7.4%, P=0.564), wound infection (RR 1.08; CI 0.65 to 1.81; I2=1.9%, P=0.755), circumferential resection margin (RR 1.10; CI 0.91 to 1.34; I2=0%, P=0.322), distal resection margin (RR 1.49; CI 0.73 to 3.05; I2=0%, P=0.272), major low anterior resection syndrome (RR 0.93; CI 0.79 to 1.10; I2=0%, P=0.386), lymph node yield (SMD 0.06; CI -0.04 to 0.17; I2=39.6%, P=0.249), 2-year DFS rate (RR 0.99; CI 0.88 to 1.11; I2=0%, P = 0.816), 2-year OS rate (RR 1.00; CI 0.90 to 1.11; I2=0%, P = 0.969), distant metastasis rate (RR 0.47; CI 0.17 to 1.29; I2=0%, P = 0.143) (Figure 3C), and local recurrence rate (RR 1.49; CI 0.75 to 2.97; I2=0%, P = 0.250). However, patients who underwent MiTME had fewer anastomotic leak rates (SMD -0.38; CI -0.59 to -0.17; I2=19.0%, P<0.0001). Conclusion: This study comprehensively and systematically evaluated the safety and efficacy of MiTME and TaTME